2018
DOI: 10.1111/jocn.14351
|View full text |Cite|
|
Sign up to set email alerts
|

Attributions of victim blame in stranger and acquaintance rape: A quantitative study

Abstract: This study has practical implications for the provision of medical services for victims of sexual assault, as it highlights problems in identifying and accessing rape victims, as well as recommending the sexual assault training of all practicing nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
(59 reference statements)
6
32
1
Order By: Relevance
“…Many studies have found that women are less likely to blame victims of acquaintance rape than men (Basow and Minieri, 2011, although gender differences only emerged in their assessment of victim blame , and not in their separate measure of victim responsibility ; Calhoun et al, 1976; Selby et al, 1977; Gerdes et al, 1988; Johnson and Jackson, 1988; Kanekar and Nazareth, 1988; Johnson et al, 1989; Bell et al, 1994; Schuller and Wall, 1998; Varelas and Foley, 1998; Lambert and Raichle, 2000; Geiger et al, 2004; Klippenstine et al, 2007; Krahé et al, 2007; Yamawaki et al, 2007; Black and Gold, 2008; Hammond et al, 2011; Casarella-Espinoza, 2015; Ferrão et al, 2016). A number of other studies, however, have produced null effects of gender on victim blaming (Gilmartin-Zena, 1983; Howells et al, 1984; Krahé, 1988; McCaul et al, 1990; Kanekar et al, 1991; Kanekar and Seksaria, 1993; Branscombe et al, 1996; Nario-Redmond and Branscombe, 1996; Hammock and Richardson, 1997; Abrams et al, 2003; Frese et al, 2004; Girard and Senn, 2008; Bieneck and Krahé, 2011; Romero-Sánchez et al, 2012; Loughnan et al, 2013; Pederson and Strömwall, 2013; Bongiorno et al, 2016; Landström et al, 2016; Qi et al, 2016; Persson et al, 2018; although these studies assessed victim culpability for being “sexually touched” at a bar and thus it is unclear if a rape has occured; Scronce and Corcoran, 1995; Stormo et al, 1997; Sims et al, 2007; Strömwall et al, 2013). No studies have found that women engaged in greater victim blaming than men.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found that women are less likely to blame victims of acquaintance rape than men (Basow and Minieri, 2011, although gender differences only emerged in their assessment of victim blame , and not in their separate measure of victim responsibility ; Calhoun et al, 1976; Selby et al, 1977; Gerdes et al, 1988; Johnson and Jackson, 1988; Kanekar and Nazareth, 1988; Johnson et al, 1989; Bell et al, 1994; Schuller and Wall, 1998; Varelas and Foley, 1998; Lambert and Raichle, 2000; Geiger et al, 2004; Klippenstine et al, 2007; Krahé et al, 2007; Yamawaki et al, 2007; Black and Gold, 2008; Hammond et al, 2011; Casarella-Espinoza, 2015; Ferrão et al, 2016). A number of other studies, however, have produced null effects of gender on victim blaming (Gilmartin-Zena, 1983; Howells et al, 1984; Krahé, 1988; McCaul et al, 1990; Kanekar et al, 1991; Kanekar and Seksaria, 1993; Branscombe et al, 1996; Nario-Redmond and Branscombe, 1996; Hammock and Richardson, 1997; Abrams et al, 2003; Frese et al, 2004; Girard and Senn, 2008; Bieneck and Krahé, 2011; Romero-Sánchez et al, 2012; Loughnan et al, 2013; Pederson and Strömwall, 2013; Bongiorno et al, 2016; Landström et al, 2016; Qi et al, 2016; Persson et al, 2018; although these studies assessed victim culpability for being “sexually touched” at a bar and thus it is unclear if a rape has occured; Scronce and Corcoran, 1995; Stormo et al, 1997; Sims et al, 2007; Strömwall et al, 2013). No studies have found that women engaged in greater victim blaming than men.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the sexual assault literature appears to offer only one clear conclusion: Victims of stranger rape are the least likely to be blamed for their assault; victims of marital rape are much more likely to be found culpable (Ewoldt et al, 2000; Monson et al, 2000). Direct comparisons between stranger rape and acquaintance rape typically find less blame in the former case (Amir, 1971; Calhoun et al, 1976; Donnerstein and Berkowitz, 1981; L’Armand and Pepitone, 1982; Janoff-Bulman et al, 1985; Tetreault and Barnett, 1987; Muehlenhard and Hollabaugh, 1988; Bridges and McGrail, 1989; Quackenbush, 1989; Pollard, 1992; Hammock and Richardson, 1997; Sinclair and Bourne, 1998; Krahé et al, 2007; Grubb and Harrower, 2008; Bieneck and Krahé, 2011; Droogendyk and Wright, 2014; McKimmie et al, 2014; Ayala et al, 2015; Stuart et al, 2016, but see Persson et al, 2018). Further, acquaintance rape victims are blamed less than marital rape victims (Ferro et al, 2008).…”
Section: Blaming the Victimmentioning
confidence: 99%
“…Specifically, gendered stereotypes and attitudes might influence the likelihood of a victim feeling able, or not, to seek help and report to the police and criminal justice services. Gender role stereotypes have developed and become entrenched attitudes that affect our responses to domestic and sexual violence in terms of victim blaming (Davies, Gilston, & Rogers, 2012;McKimmie, Masser, & Bongiorno, 2014;Ståhl, Eek, & Kazemi, 2010), service response (Persson, Dhingra, & Grogan, 2018;Shechory & Idisis, 2006), and punitive action (Radačić, 2014).…”
Section: Gendered Stereotypes and Perceptions Of Violencementioning
confidence: 99%
“…In “Attributions of victim blame in stranger and acquaintance rape: A quantitative study” by Persson, Dhingra, and Grogan (2018) which was published in volume 27, issue 13–14 in July 2018, the original Table 1 (descriptive results) contained some incorrect numbers. The correction has revised this.…”
Section: N M Sdmentioning
confidence: 99%